Mechanical and thermal properties of short sugar palm (Arenga pinnata MERR.) fibre-reinforced high impact polystrene composites - Dandi Bachtiar, (2012)
Sugar palm fibre (SPF) is a promising natural fibre used in reinforcing polymer matrix composites. The fibre has good tensile properties and could also be suitable as reinforcing agents in composite materials. This research is important because no study has been conducted about the using of sugar palm fibre to reinforced high impact polystyrene (HIPS) composites previously. New natural composites of sugar palm fibre (SPF) reinforced high impact polystyrene (HIPS) matrix have been produced by using melt mixing and compression moulding method. Tensile, flexural, and impact tests were performed to determine the mechanical properties, while dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA) were performed to determine the thermal properties of SPF-HIPS composites by varying the sugar palm fibre contents. It was found that the increase in fibre loading on HIPS matrix enhanced the tensile and flexural modulus of the composites. However, tensile strength decreased with the increase in fibre loading due to poor compatibility of interface between fibre and polymer surfaces. The flexural strength also increased. However, all of the values of flexural strength of SPF-HIPS composites were lower than the pure HIPS matrix. The addition of short SPF decreased the impact strength of these composites. It was found that from the dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA) the SPF-HIPS composites showed better thermal stability than pure HIPS matrix. The moisture content of the SPF-HIPS composites increase and this behavior contribute to weakness in strength. The major barrier in utilising natural fibres in reinforcing polymer composites is compatibility issue. It is because the weak interfacial bonding between hydrophilic fibres and hydrophobic polymers. The alkali treatment and compatibilizing agent were performed to the SPF-HIPS composites at the fibre content of 40%. The alkali treatment was performed by immersing fibres in 4% and 6% alkali solution, and the incorporation of 2% and 3% polystyrene-block-poly(ethylene-ran-butylene)-blockpoly( styrene-graft-maleic-anhydride) were used as compatibilizing agent. Both alkali treatment and compatibilizing agent treatment increased the tensile strength of composites, while the alkali treatment at the 4% level showed the highest tensile strength, improvement of about 35% from untreated composites. Therefore, alkali treatment with 6% NaOH solution could improve the flexural strength, flexural modulus and impact strength of the composites from the untreated composites by 12%, 19% and 34% respectively. Compatibilizing agent showed the improvement on the impact strength, i.e 6% and 16% improvement for 2% and 3% MAH respectively, meanwhile, no enhancement of the composites properties when subjected to flexural properties testing. Finally, modification of the SPF-HIPS composites, using the compatibilizing agent and the fibres treated with alkali has brought a slight improvement to the peak temperature of decomposition of composites. It can be stated that the the modification of composites with alkaline treatment and compatibilizing agent on the high impact polystyrene composites resulted in higher thermal stability of the composites than the high impact polystyrene polymer alone.